The web-based library instruction in academic libraries in Malaysia / Noor Hidayat Adnan - Adnan, Noor Hidayat (2001)
The emergence of the Internet and WWW has affected all functions of an academic library, particularly library instruction. This technology has led to the utilisation of new tools and methods for providing library instruction to the users. This study examined the used of the web-based library instruction in Malaysian academic libraries. The objective of the study was to examine the current practices of delivering library instruction in academic libraries. The findings have presented the overview on the planning, delivery and content of library instruction programmes in academic libraries. The study aimed to evaluate the general design, interactivity, presentation mode, tutorial structure, graphical interface and the technical performance of the academic library websites. The study further examined the issues relating to web-based library instruction and the strengths and weaknesses presented on library instruction programmes. The study has revealed the potential and benefits of web-based library instruction. A total of 40 professional librarians working in the reference department of seven Malaysian academic libraries located in the Klang Valley participated in the study. Respondents felt that the web has contributed positively to library instruction and has enhanced their effectiveness and efficiency. However, respondents disagreed that the web should completely replace traditional library instruction programmes. In most of these academic libraries, traditional library instruction programmes such as guided group tour, video or slide presentation, and self-guided tour that using printed pamphlets for self-directed or self-guided are still be conducted. Respondents also felt that professional librarians should possess good computing and web use skills for providing effective library instruction to the users.